Nurse managers' perceptions and experiences regarding staff nurse empowerment: a qualitative study - Van Bogaert, Peter; Peremans, Lieve; de Wit, Marlinde; Van heusden, Danny; Franck, Erik; Timmermans, Olaf; Havens, Donna S. (Frontiers in Psychology, 2015)
Aim: To study nurse managers' perceptions and experiences of staff nurse structural empowerment and its impact on the nurse manager leadership role and style. Background: Nurse managers' leadership roles may be viewed as challenging given the complex needs of patients and staff nurses' involvement in both clinical and organizational decision-making processes in interdisciplinary care settings. Design: Qualitative phenomenological study. Methods: Individual semi-structured interviews were conducted with 8 medical or surgical nurse managers in a 600-bed Belgian university hospital between December 2013 and June 2014. This hospital was undergoing conversion from a classical hierarchical, departmental structure to a flat, interdisciplinary model. Results: Nurse managers were found to be familiar with the structural empowerment of clinical nurses in the hospital and to hold positive attitudes toward it. They confirmed the positive impact of empowerment on their staff nurses, as evidenced by increased responsibility, autonomy, critical reflection and enhanced communication skills that in turn improved the quality and safety of patient care. Structural empowerment was being supported by several change initiatives at both the unit and hospital levels. Nurse managers' experiences with these initiatives were mixed, however, because of the changing demands with regard to their manager role and leadership style. In addition, pressure was being experienced by both staff nurses and nurse managers as a result of direct patient care priorities, tightly scheduled projects and miscommunication. Conclusion: Nurse managers reported that structural empowerment was having a favorable impact on staff nurses' professional attitudes and the safety and quality of care in their units. However, they also reported that the empowerment process had led to changes in the managers' roles as well as daily practice dilemmas related to the leadership styles needed. Clear organizational goals and dedicated support for both clinical nurses and nursing unit managers are imperative to maintaining an empowering practice environment which can ensure the best care and healthy, engaged staff.